Counteraction to Crimes of a Sexual Nature against Minors in the Republic of Kazakhstan: International Practice and National Peculiarities - SHAIMERDENOV, Bolat Erkenovich (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017DO - 10.14505/jarle.v8.7(29).22, 2017)
The criminological and criminal law counteraction to criminal offences of a sexual nature against minors are studied in this article. The aim of the article is to analyze the methods of preventing crimes against the sexual inviolability of minors, and to study the legal norms on the crimes against the sexual inviolability of minors contained in the national criminal legislation of Kazakhstan and in the legislation of a number of foreign countries. The international organizational and legal experience of protecting minors from sexual assault, the norms of the criminal legislation of Kazakhstan and the legislation of a number of foreign countries on crimes against the sexual inviolability of minors are studied herein; the conclusions and recommendations for the further improvement of the preventive measures and the criminal legal protection of minors from encroachments on their sexual inviolability are formulated. Based on the study of the research materials on criminology and the experience of foreign countries in the field of counteracting crimes against the sexual inviolability of minors, the methods of eliminating the causes and conditions for criminal acts of the category in question are suggested, the proposals for further improvement of the criminal legislation of the Republic of Kazakhstan in terms of protection of minors from sexual assault are formulated by the author. In particular, the necessity of formulation of a number of independent norms on crimes of a sexual nature against minors, taking into account the age characteristics of victims, and also the necessity to increase the criminal liability for incest with the participation of a minor is substantiated. The main provisions and conclusions of this article can be used in scientific and pedagogical activities when considering the issues of crime prevention and the comparative characteristics of the norms on crimes against the sexual inviolability of minors in Kazakhstan and foreign countries, as well as in the course of subsequent reforming of the criminal legislation norms in the field of sexual freedom and sexual inviolability of the person.